European Symposium on Precision Medicine in Allergy and Airways Diseases: Report of the European Union Parliament Symposium (October 14, 2015). Issue 5 (8th March 2016) - Muraro, A.; Fokkens, W. J.; Pietikainen, S.; Borrelli, D.; Agache, I.; Bousquet, J.; Costigliola, V.; Joos, G.; Lund, V. J.; Poulsen, L. K.; Price, D.; Rolland, C.; et al.
Abstract: The European Academy of Allergy and Clinical Immunology (EAACI), the European Rhinologic Society (ERS), and the European Medical Association (EMA) organized, on October 14, 2015, a symposium in the European Parliament in Brussels on Precision Medicine in Allergy and Airways Diseases, hosted by MEP David Borrelli, and with active participation of the EU Commissioner for Health and Food Safety Vytenis Andriukaitis, MEP Sirpa Pietikainen, Chair of the European Parliament Interest Group on Allergy and Asthma, the European Respiratory Society (ERS), the European Federations of Allergy and Airways Diseases Patients Associations (EFA), the Global Allergy and Asthma European Network (Ga2len), Allergic Rhinitis and Its Impact on Asthma (ARIA), and the Respiratory Effectiveness Group (REG). The socioeconomic impact of allergies and chronic airways diseases cannot be underestimated, as they represent the most frequently diagnosed chronic noncommunicable diseases in the EU; 30% of the total European population is suffering from allergies and asthma, and more than half are deprived from adequate diagnosis and treatment. Precision medicine represents a novel approach, embracing four key features: personalized care based on molecular, immunologic, and functional endotyping of the disease, with participation of the patient in the decision‐making process of therapeutic actions, and considering predictive and preventive aspects of the treatment. Implementation of precision medicine into clinical practice may help to achieve the arrest of the epidemic of allergies and chronic airways diseases. Participants underscored the need for optimal patient care in Europe, supporting joint action plans for disease prevention, patient empowerment, and cost‐effective treatment strategies.